Migration assay on primary culture isolated from patient's primary breast cancer tissue - ED Yuliana; A Bustami A Bustami; HP Tantry (Faculty of Medicine, Universitas Andalas, 2014)
Background: Migration is an essential component of breast cancer metastasis, which studyhas been concentrated on culture of established breast cancer cell lines that do not accuratelyrepresent the sophistication and heterogeneity of patient's breast cancer. An attempt toperform migration assay using Boyden Chamber Assay (BCA) on primary culture originatingfrom patient's breast cancer tissue was developed to accommodate upcoming study of breastcancer migration in lndonesian patients.Methods: Pathologically proven primary breast cancer tissue samples were obtained fromCiptomangunkusumo Hospital during core (n=4) and incisional (n=3) biopsies of stage llAup to stage lllA breast cancer patients. Following biopsy, the breast cancer tissue samplesunderwent processings to isolate the cancer cells. These cancer cells were -then resuspendedwithin Dulbecco's modified Eagle's medium (DMEM) ahd cultured in 12-well plate. The growthof primary culture were observed and compared between the core biopsy and the incisionalbiopsy specimens. Optimization of BCA method was later performed to investigate themigration of the breast cancer primary culture towards different experirnental conditions, whichwere control, Fetal Bovine Serum (FBS), and Stromal Derived Factor-l (SDF-1). Two differentnumber of breast cancer cells were tested for the optimization of the BCA, which were 1 x 105and3x105cells.Results: None of the culture performed on core biopsy specimens grew, while one out ofthree incisional biopsy specimens grew until confluence. The one primary culture that grewwas later assesed using BCA to assess its migration index towards different experimentalconditions. Using 1 x 10s breast cancer cells in the BCA , the result of the absorbance level ofmigrated cells showed that the migration towards SDF-1 (0.529) nearly doubled the migrationtowards controlmedium (0.239) and FBS (0.209). Meanwhile, the absorbance levelwas simiiarbetween the control medium (1.050), FBS (1 .103), and SDF-1 (1 .104) when the same test wasrun with 3 x 105 breast cancer cells.Discussion: Breast cancer tissue collected using incisional biopsies hao better chance togrow in primary culture than those collected using core biopsies, possibly due to the differencein the amount of tissue extracted. Consistent with previous research, patient's breast cancercells was shown to migrate more towards the chemokine ligand SDF-1, as compared to controlmedium and FBS. The number of breast cancer cells run in the BCA also affected the result ofthe migration assay, where 1 x 10s cells showed a superiority as compared to 3 x 105 cells inshowing the migration difference between the different experimental conditions.MKA, Volume 37, Nomor.Supl. 2, November 2014ED Yulian dkk